Math, asked by saumyapareek06, 9 months ago

plz solve this question​

Attachments:

Answers

Answered by ashajuneja09
1

I think you will like me answer please marked as brainliest

Attachments:
Answered by ishigoel02
1

Answer:

a=14,b=0

Step-by-step explanation:

on cross multiplying we get  \frac{ {(2 +  \sqrt{3} )}^{2}  +  {(2 -  \sqrt{3} )}^{2}  }{(2 + \sqrt{3}  )(2 -  \sqrt{3} )}  = a +b  \sqrt{3}

we know that (a+√b)(a-√b)=a²-b

 \frac{4 + 3 + 4 \sqrt{3} + 4 + 3 - 4 \sqrt{3}  }{ {2}^{2}  -  { \sqrt{3} }^{2} }  =  a+ b \sqrt{3}

on simplifying we get

 \frac{4 + 3 + 4 \sqrt{3} + 4 + 3 - 4 \sqrt{3}  }{ 4 -  3}  = a + b \sqrt{3}

 \frac{14 + 0 \sqrt{3} }{1}  = a + b \sqrt{3}

14 + 0 \sqrt{3}  =  a + b\sqrt{3}

on comparing we get a=14 and b=0

Please mark it as brainliest

Thanks

Similar questions